(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
The study examined the adoption of soybean products among women in Onitsha North Local Government Area of Anambra State, Nigeria. Specifically, it described the socioeconomic characteristics of the respondents, identified the type of soybean products available in the area, determined the source of information of the soybean products, ascertained the level of adoption of soybean products and identified the major constraints to the adoption of soybean products in the area. Purposive and simple random methods were used to select 50 respondents. Data were collected using structured questionnaire and personal interview and analyzed using descriptive statistics such as percentage, frequency distribution and mean scores. Findings show that 91.0% of the respondents were within the age range of 30-49 years, while the mean age of the farmers was 45.43 years. Extension agents (90.0%) and friends/relatives (80.0%) were the major source of information. Based on the level of adoption of soybean products, the farmers’ adopted only five soybean products, which included soymilk, soybean cake, soybean oil, soybean nut and soy flour. The major constraints against adoption of soybean product were poor extension service to assist farmers (x=3.7), lack of awareness of the soybean products (x=3.3) and lack of capital (x=3.3). In line with the findings, the study therefore recommends that extension agent needs to re-package and dynamically disseminate information, educate and re-educate farmers on several health benefit of soybean use in order to upgrade farmers’ awareness and subsequently their adoption. Int. J. Agril. Res. Innov. Tech. 9(2): 30-34, December 2019